Assessment Of Knowledge and Skills of Counselling Among Link Workers of Link Workers' Scheme For HIV/Aids in Rural Areas of Surat District - Binita Desai; Rohit Parmar; JK Kosambiya; Priti Solanky; Shailesh Prajapati; SL Kantharia (Medsci Publications, 2012)
Background: The Link Worker Scheme envisioned a new cadre of worker, the Link Worker (LW), that was introduced at rural level. Link Workers was a motivated, community level, paid female and male youth workers with a minimum level of education. They can help in prevention of HIV by their counselling services among rural areas. Methodology: Due to few vacant posts, total 183 participants from 70 villages had taken part in the study; Their knowledge regarding counselling and counselling skills were assessed in two stages as counselling was the one of the main cornerstone of HIV prevention programme. In first part all participants were assessed for knowledge of counselling in a pre designed proforma while later on 25% of the participants were assessed for their counselling skill. Majority of the participants had average knowledge for almost all domains related to skills of counselling. Result: Around 65% of the study participants preferred the isolated place for counselling. 37.65 of participants reported that they were comfortable while talking to Female Sex Workers, Man having Sex with Man and Transgender. 51.3% reported that they had difficulty in counselling clients for referral services. Recommendations: It is essential to refresh training of counselling after induction training to enhance and up date their knowledge and skills of counselling. Exposure visits to HIV care centres can also improve the same.